Shaoyao Decoction Inhibits Inflammation and Improves Intestinal Barrier Function in Mice With Dextran Sulfate Sodium-Induced Colitis - Chi, Honggang; Wang, Dan; Chen, Mengting; Lin, Jiantao; Zhang, Shuhua; Yu, Fengyan; Zhou, Jun; Zheng, Xuebao; Zou, Ying (Frontiers in Pharmacology, 2021)
Shaoyao decoction (SYD), a classical traditional Chinese medicine formula, is effective for the treatment of inflammatory bowel disease (IBD). This study was designed to investigate the therapeutic effects and possible mechanism of SYD on IBD. Dextran sulfate sodium (DSS, 3.5%) was used to induce colitis in C57BL/6 mice. Disease phenotypes were investigated based on body weight, rectal bleeding, diarrhea, colon length, and microscopic and macroscopic scores. Additionally, the presence of proinflammatory cytokines, immune cell infiltrates, intestinal cell proliferation, apoptosis, epithelial permeability, signal transducer and activator of transcription 3 (STAT3) and nuclear factor- κB (NF-κB) signaling, and intestinal mucosal barrier function were investigated. The administration of SYD significantly ameliorated the clinical symptoms, suppressed the levels of proinflammatory cytokines, and reduced immune cell infiltrates into colonic tissues of DSS-induced colitis. SYD also significantly reduced the DSS-induced activation of STAT3 and NF-κB signaling. Furthermore, SYD promoted epithelial integrity by regulating epithelial cell apoptosis and epithelial permeability. Finally, we demonstrated that SYD protected intestinal barrier function by significantly regulating the mucus layer genes Muc1, Muc2, Muc4, and Tff3 as well as the epithelial barrier genes ZO-1 and Occludin. Our results indicate that SYD had a protective role in DSS-induced colitis, which is attributable to its anti-inflammatory activity and intestinal barrier function enhancing effects. These results provide valuable insights into the pharmacological actions of SYD in the treatment of IBD.